NILAI – NILAI PENDIDIKAN KARAKTER DALAM KESENIAN REYOG PONOROGO - Nayif Al Rosidin (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
Reyog nowadays is merely seen by the public only as an art of entertainment and beauty, even though researchers believe that many values can be taken from the traditional art. As the generation of future who are obliged to maintain and preserve it, they must begin to see and understand this art from various perspectives. From the results of the study found that the values of character education in Reyog Ponorogo in terms of the symbolic meanings are Religiousity, symbols that show the value of religious characters one of which, Reyog is taken from Arabic (Riyyuq). Tolerance, Reyog gamelan which is based on pelog and slendro illustrates the difference situation. When it is played with a sense of tolerance, it can walk in harmony and go well together. Discipline and hard work, contained in the story of the figure Prabu Kelono Sewandono and his patih Pujangganong who have the spirit of discipline and hard work in running the government of the Kingdom of Bantarangin. Creativity, as Patih Pujangganong is creative as evidenced by the creation of Reyog art from his effort. The spirit of nationalism and love of the motherland, Reyog figures such as Warok, Pujangganong, Jathilan, etc who always acted faithfully to the kingdom and the king, showed a symbol of the spirit of nationalism and love of the motherland. Responsibility, Kelono Sewandono as a king has responsibility for the kingdom he dreams of. Thus, it can be concluded that the art of Reyog Ponorogo is very relevant to the objectives of Islamic Education.